PENGARUH APLIKASI KONSORSIUM ISOLAT BAKTERI TERPILIH DAN JENIS PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annum) - Dermiyati, Dermiyati; Nasution, Muhammad Fajar Ismail; Hendarto, Kus; Arif, Mas Ahmad Syamsul (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Low production of red chili (Capsicum annuum L.) remains a major constraint in meeting market demand and is frequently attributed to suboptimal soil fertility. Enhancing soil fertility through appropriate fertilization strategies, including both chemical and organic inputs, is therefore critical to improving crop yield. In addition, microbial consortia with plant growth-promoting potential are increasingly explored as biofertilizer alternatives to support sustainable agriculture. This study investigated the effects of selected bacterial isolate consortia, types of fertilizers, and their interactions on the growth and production of red chili plants. A 4 × 3 factorial Randomized Group Design with three replications was employed. The first factor was the bacterial consortium: no consortium (K0), consortium from pineapple rhizosphere (PR) (K1), consortium from Empty Fruit Bunches (EFB) (K2), and a combination of PR + EFB (K3). The second factor was fertilizer type: chemical fertilizer (P1), sterile organonitrophos fertilizer (P2), and non-sterile organonitrophos fertilizer (P3). The results indicated that the application of bacterial isolate consortia did not significantly influence red chili growth or production. However, sterile organonitrophos fertilizer enhanced chili production, while non-sterile organonitrophos fertilizer produced the best outcomes for plant growth and soil organic-C content. No significant interaction was observed between bacterial consortia and fertilizer type for any measured parameter. These findings underscore the greater role of organic-based fertilizers, particularly non-sterile organonitrophos, in improving soil quality and crop performance, thereby offering a sustainable alternative to chemical fertilization for red chili cultivation.